ThreeCle Model: Penerapan Kepemimpinan di PrimeBiz Hotel Surabaya - Anshori, Mohamad Yusak (Universitas Nahdlatul Ulama Surabaya, 2022)
Primebiz Hotel Surabaya (PBS) is service company (hotel) which its service quality is determined by its human resources. The quality of its human resource much be influenced by hotel leader. Leadership has an important role in the company since leadership will influence the management style, corporate culture, working environment, and values of the company. To resolve human resources management problems, it uses threecle (three circle) model. This model was shaped from the practical management that has been implemented at Primebiz Hotel Surabaya (PBS). In this study, various leadership models are elaborated and discussed at the PBS. The result of the implementation of this model much support the hotel management in making decision and increasing the efficiency as well as the effectiveness in the hotel operation. Implementing this model, it means increasing wisdom and fairness in making decision, especially related with the human resources issues.